LHC multijet events as a probe for anomalous dimension-six gluon interactions - Krauss, Frank; Kuttimalai, Silvan; Plehn, Tilman (Physical review, 2017)
Higher-dimensional multigluon interactions affect essentially all effective Lagrangian analyses at the LHC. We show that, contrary to common lore, such operators are best constrained in multijet production. Our limit on the corresponding new physics scale in the multi-TeV range exceeds the typical reach of global dimension-six Higgs boson and top analyses. This implies that the pure Yang-Mills operator can safely be neglected in almost all specific higher-dimensional analyses at Run II.